Evaluate the effectiveness technology for the treatment of oily wastewater. (9th August 2022) - Almutairi, Meshari
Abstract: This work deals with the treatment of oily wastewater produced from the washing of oil-contaminated soil. Untreated oily wastewater contains toxic compounds that might be mutagenic or carcinogenic as total petroleum hydrocarbon (TPH) and heavy metals. Based on the water quality analysis, the tested samples contained a high concentration of TPH, chemical oxygen demand (COD) and turbidity with an average value of 67, 500 mg/l, 48, 240 mg/l and 176 (nephelometric turbidity unit, NTU), respectively. Several technologies were used, such as centrifuging, powdered activated carbon (PAC) and sawdust. The mean values of COD values for sawdust, centrifuging and PAC were 41, 067, 25, 600 and 13, 133 mg/l, respectively. The present study indicated that the coagulation/flocculation processes were more efficient by using aluminium sulphate alum, while the preliminary conclusion derived was that the secondary treatment using an aeration system is capable of lowering the COD values as well as increasing the flocculent mass floc well equal to 4, 784 mg/l and 0.69 g, respectively. The microbial seed was able to degrade the biosurfactant, which allows the stability of oil emulsion to be broken down and released easily. HIGHLIGHTS: Centrifuging sawdust and PAC were carried out to treat oily wastewater. The mean values of COD for sawdust, centrifuging and PAC were 41, 067, 25, 600 and 13, 133 mg/L. The combination of aeration with coagulation/flocculation enhanced the treatment process. Microbial seed effect on the stability of oil emulsion by degrading saponin in wastewater. Graphical Abstract